2010
DOI: 10.1016/j.tet.2010.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Tautocrowns: a concept for a sensing molecule with an active side-arm

Abstract: A new sensing molecule containing aza-15-crown-5 as a receptor and 4-(phenyldiazenyl)naphthalen-1-ol as a signal converter has been synthesized. In the free ligand, the hydrogen bonding between the tautomeric OH group and the nitrogen atom from the macrocycle fully shifts the tautomeric equilibrium towards the enol form. The complexation reverses the equilibrium as a result of the strong interaction between the metal ion captured in the macrocyclic moiety and the tautomeric carbonyl group. The complex formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…The product was purified by HPFC on silica gel: mobile phase with a gradient of polarity from cyclohexane−acetone 90:10 to cyclohexane−acetone 20:80. The NMR spectra were identical with the previously reported: 28 Synthesis of BA15C5. The known compound BA15C5 was obtained by alkylation of 1-aza-15-crown-5 with benzyl bromide in dry dichloroethane in the presence of K 2 CO 3 as a base.…”
Section: ■ Experimental Sectionsupporting
confidence: 54%
See 1 more Smart Citation
“…The product was purified by HPFC on silica gel: mobile phase with a gradient of polarity from cyclohexane−acetone 90:10 to cyclohexane−acetone 20:80. The NMR spectra were identical with the previously reported: 28 Synthesis of BA15C5. The known compound BA15C5 was obtained by alkylation of 1-aza-15-crown-5 with benzyl bromide in dry dichloroethane in the presence of K 2 CO 3 as a base.…”
Section: ■ Experimental Sectionsupporting
confidence: 54%
“…The synergist 2-[(1-aza-15-crown-5)-1-ylmethyl)]-4-(phenyldiazenyl)-naphthalen-1-ol (PDN1A15C5) is a red crystalline compound insoluble in water and was obtained as previously reported. 28 Shortly, 1-naphthol was subsequently submitted to diazo coupling and Mannich reaction with 1-aza-15-crown-5 (Scheme 1). The product was purified by HPFC on silica gel: mobile phase with a gradient of polarity from cyclohexane−acetone 90:10 to cyclohexane−acetone 20:80.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This happens in 12 ( Figure 1.4), where, compared to the parent compound 13, the intramolecular hydrogen bonding between the tautomeric OH group and the basic nitrogen from the side arm leads to the disappearance of the keto tautomer [12,13]. The situation changes upon protonation (or complex formation) -the basic nitrogen is protonated and a new hydrogen bonding, this time between protonated sidearm and tautomeric carbonyl group, shifts the equilibrium toward the keto form 12H + .…”
Section: Causes Of Reversal In Tautomeric Form: Selective Stabilizatimentioning
confidence: 99%
“…The NMR spectra of the products in 10 À1 M concentration in deuterochloroform showed sharp and well defined signals consistent with enol forms. It can be suggested that azo dyes 3 exist in chloroform as single enol form, as was observed for analogues with flexible side-chain 1 [18] and 2 [19], and contrary to unsubstituted 4-phenylazo-1-napthol and 2-phenylazo-1-napthol, where both tautomers coexist and the populations of the keto forms are calculated from 13 C and 15 N spectra [23,24]. The preferred conformations of amide side chains (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Recently, the concept for a tautomeric switch, where a directed shift in the position of the tautomeric equilibrium can be achieved through protonation and/or complexation, was proven by attaching of a flexible nitrogen linked piperidine [18] (1, Fig. 1) or 1-aza-15-crown-5 [19] (2) fragment to 4-(phenyldiazenyl)naphthalen-1-ol. Both compounds were isolated as pure enol forms due to strong hydrogen bonding between tautomeric hydroxyl group and the side chain nitrogen atom and were fully converted to ketotautomers, which, to the best of our knowledge, present the first examples of an active side-arm containing chemosensors with significant bathochromic and hyperchromic effects of the absorption maximum upon protonation or complexation.…”
Section: Introductionmentioning
confidence: 99%